THE EFFECT OF JOB SATISFACTION AND ORGANIZATIONAL COMMITMENT ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR IN EMPLOYEES - Wahyuni, Winda Sri; Dirbawanto, Nana Dyki (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2022)
Organizational Citizenship Behavior is a trait that describes a person's high initiative and heightened awareness of the state of his organization. OCB can result from a variety of organizational factors, including employee job satisfaction and high organizational commitment. Satisfied employees will work hard to complete their tasks and may even go above and beyond. Similarly, a person with a strong commitment to his organization will do anything to advance his company due to his faith in the organization. This study aims to analyze how the effect of job satisfaction and organizational commitment on organizational citizenship behavior in employees of PT. Palarudhibi Teguh Makmur. This is a quantitative research involving 67 respondents as research samples. Sampling was done through a saturated sample technique. Collecting data through questionnaires distributed to respondents. The method of data analysis utilized an instrument test of reliability and validity, a test of classical assumptions, and a test of hypotheses using multiple linear regression analysis. The findings of this study indicate that job satisfaction and organizational commitment have a significant effect, either individually or jointly, on the organizational citizenship behavior of PT. Palarudhibi Teguh Makmur Focal Point Medan's employees by a margin of 25,7%.